2015
DOI: 10.1136/bmjdrc-2015-000108
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for management of diabetes during Ramadan: update 2015

Abstract: Since the first ADA working group report on the recommendations for management of diabetes during Ramadan in 2005 and our update in 2010, we received many inquiries asking for regular updates on information regarding education, nutritional habits and new oral and injectable agents that may be useful for the management of patients with diabetes during Ramadan. Patients can be stratified into their risk of hypoglycemia and/or complications prior to the start of the fasting period of Ramadan. Those at high risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
128
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(135 citation statements)
references
References 34 publications
1
128
2
4
Order By: Relevance
“…Subjects were asked to report any symptomatic or serious hypoglycaemic events defined as hypoglycaemia associated with severe cognitive impairment requiring external assistance for recovery [7] during CGM recording days or fast breaking during Ramadan month. Education and advice about adjustment of anti-diabetic treatment and doses for the Ramadan period were given to all subjects before Ramadan started according to clinical guidelines [8]. …”
Section: Methodsmentioning
confidence: 99%
“…Subjects were asked to report any symptomatic or serious hypoglycaemic events defined as hypoglycaemia associated with severe cognitive impairment requiring external assistance for recovery [7] during CGM recording days or fast breaking during Ramadan month. Education and advice about adjustment of anti-diabetic treatment and doses for the Ramadan period were given to all subjects before Ramadan started according to clinical guidelines [8]. …”
Section: Methodsmentioning
confidence: 99%
“…The use of DPP4 inhibitor has been shown to have similar glycemic efficacy compared to insulin secretagogue in the general population, with an extra advantage of lower hypoglycemic risk [22][23][24]. DPP4 inhibitors are also considered safer during Ramadan with no major dose adjustment needed [25]. Risk of hypoglycemia is increased during Ramadan because of daytime fasting.…”
Section: Discussionmentioning
confidence: 97%
“…(10,14) Studies have shown that interventional education programmes, such as those used in the Ramadan Education and Awareness in Diabetes study and the Ramadan Prospective Diabetes Study, (15,16) were able to reduce the high complication rates that were observed during fasting (as demonstrated in the EPIDIAR study (3) ). Other studies have also shown that there is a need for preparation (e.g.…”
Section: Discussionmentioning
confidence: 99%